ACCEPTING THE AUTONOMY’S PILLAR ‘FREEDOM OF THE WILL’ IN MORAL EDUCATION BASED ON ISLAMIC MYSTICISM: THE CAPACITY OF SOUTH EAST ASIA’S - Toosi, Javad Fakhkhar; Jamil, Asyraf Isyraqi; Mohd Yusoff, Mohd Yakub @ Zulkifli (Journal of Islamic Educational Research, 2018)
The current article seeks to demonstrate the possibility of modernizing Islamic moral education in a special part of Muslim lands namely South East Asia by adapting to the theory of autonomy (moral independence) based on the unique capacity of Islamic mysticism. The method of this research is qualitative. The purpose of the article is to prove that due to the wide mysticism found in the South East Asia region, such as Malaysia, there is a large capacity in this region for the develpopment of Islamic moral education and the acceptance of main pillar of autonomy namely freedom of the will, which is an important step in the modernization of Islamic education. The result of this article is that the freedom of the will means that the moral deed must be performed solely for the purpose of its duty and Islamic mysticism precisely explains such motivation for the mystic and thus becomes consistent with the theory of autonomy in this regard. Another result of this article is that South East Asia has the willingness of such a movement (modernization of Islamic moral education with autonomy’s acceptance). The summary of the article is that aligning the Islamic mysticism with the autonomy which symbolizes the modern education on the one hand and the intense mystical tendencies in the South East Asia regions on the other hand provide the proper grounds for both of education scholars and policy makers to begin the movement towards the modernization of education.